Photochemical ligation meets nanocellulose: a versatile platform for self-reporting functional materials. Issue 3 (24th April 2018) - Hoenders, Daniel; Guo, Jiaqi; Goldmann, Anja S.; Barner-Kowollik, Christopher; Walther, Andreas
Abstract : The fusion of tetrazole/maleimide-based photochemical ligation (self-reporting, selective) with cellulose nanofibrils (good mechanical properties, biocompatible, sustainable) establishes a versatile platform for bio-based advanced materials. Abstract : The sustainable origin and highly promising mechanical and functional properties of cellulose nanofibrils (CNFs) attract significant interest for the construction of advanced functional materials. One key aspect of promoting the functionality of CNF-based materials is to implement sophisticated, facile and versatile chemical functionalization principles for application-targeted modification of CNF properties, independent of whether aiming for functional surfaces, hydrogels or bulk materials. We herein merge, for the first time, a self-reporting photo-induced modular ligation (the UV-induced nitrile imine-mediated tetrazole/ene cycloaddition, NITEC) with CNFs to control chemical functionality in space and time with the possibility for a macroscopic fluorescence readout of the reaction progress. We discuss this hetero-complementary photo-conjugation with respect to the immobilization of photoactive tetrazole units on CNFs in bulk and dispersion, and demonstrate the application for three important CNF-based material classes (surfaces, hydrogels and bioinspired nanocomposites) by modification with photo-complementary maleimide-tethered functional moieties. In addition to realizing selective biorecognition patterns on transparent nanopapers, we present photo-induced hydrogelation relevant for biomaterials, as well as mechanical stiffening in bioinspired nanocomposites in the bulk. The photochemical ligation proceeds smoothly in all three materials with vastly different dynamics (solution to bulk) and hence establishes a platform methodology to promote the self-reporting functionalization of diverse CNF-based materials.